ANALYSIS OF DETERMINANTS OF GROSS REGIONAL DOMESTIC PRODUCT OF DISTRICTS/CITIES IN THE PROVINCE OF BALI IN 2019-2023 - Ni Putu Ari Cipta Dewi; Putu Ayu Pramitha Purwanti (Adisam Publisher, 2025)
Regional economic development is an important foundation in promoting equitable growth in each region. Bali Province as a national leading tourism area has experienced fluctuating economic dynamics, especially during the COVID-19 pandemic which has had a significant impact on strategic sectors. Inequality between districts/cities as well as differences in fiscal capabilities and the quality of human resources are also concerns in the formulation of regional development policies. The purpose of this study is to analyze Investment, Tourism Sector, Human Development Index (HDI), Labor Force Participation Rate (LFPR), and Regional Original Income (ROR) on Regency/City Gross Regional Domestic Product (GDP) in Bali Province in 2019–2023. This study uses secondary data with a quantitative approach and panel data method. The data used consisted of 45 observations covering nine districts/cities over five years. The data analysis techniques used were descriptive statistical analysis and panel data regression with a fixed effect model (FEM) approach based on relevant tests. The results of the study show that: 1) Investment, Tourism Sector, HDI,LFPR, and ROR simultaneously have a significant positive effect on the GDP of Regencies/Cities in Bali Province; 2) Partially, Investment, Tourism Sector, HDI, LFPR and ROR have a positive and significant effect on GDP. The results of this research are expected to be considered for local governments in formulating regional economic development policies based on strategic sectors and improving the quality of human resources to achieve sustainable and inclusive growth.